Inhibitory Activity of Myricetin and Chlorogenic Acid against Dengue Virus NS2b/NS3 Protease through In Silico Approaches (Journal of Institute of Science and Technology, 2024)
The resurgence of dengue virus (DENV) infection poses a significant global health threat, exacerbated by urbanization and climate change. Flaviviridae family virus, DENV infection can be asymptomatic in some cases while it can be lethal in others. More serious symptoms include dengue hemorrhagic fever, dengue shock syndrome, and liver damage. Despite these worrying features, no specific drug has been approved till now. People have been relying on antipyretic drugs only. This study explores the inhibition potential of natural compounds myricetin and chlorogenic acid against DENV using computational analysis. Molecular docking and molecular dynamics simulations were employed to assess their inhibitory effects on a crucial enzyme NS2B/NS3 protease of DENV. NS2B/NS3 protease, highly conserved in the DENV serotypes, plays a vital role in viral replication and it acts as an excellent drug target. The phytochemicals myricetin (MYR) and chlorogenic acid (CGA) have docking scores of -7.9 kcal/mol and -7.1 kcal/mol targeting NS2B/NS3 protease, respectively. By analyzing RMSD, RMSF, RG, SASA and H-bonding, MYR possesses greater compactness and stability in comparison with quercetin and CGA throughout the MD simulation. The NS2B/NS3 protease in complex with MYR and CGA shows end-state MM/GBSA free energy of -25.053.19 kcal/mol and -20.22±3.02 kcal/mol, respectively. ADMET analysis shows that the proposed compounds offer good bioavailability scores. CGA with a higher LD50 value (5000 mg/kg) appears in predicted toxicity class 5 whereas quercetin and MYR with lower LD50 value (159 mg/kg) appear in the toxicity class 3. The results suggest that CGA and MYR exhibit strong binding affinities and stable interactions, highlighting their potential as DENV inhibitors. Further experimental verifications will be necessary to determine the effectiveness of such drug candidates against DENV.